Promising therapeutic mechanism for Chinese herbal medicine in ameliorating renal fibrosis in diabetic nephropathy - Wang, Shengju; Qin, Shuai; Cai, Baochao; Zhan, Jihong; Chen, Qiu (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is one of the most serious chronic microvascular abnormalities of diabetes mellitus and the major cause of uremia. Accumulating evidences have confirmed that fibrosis is a significant pathological feature contributes to the development of chronic kidney disease in DN. However, exact mechanism of renal fibrosis in DN is still unclear, which greatly halt treatment of DN. Chinese herbal medicine (CHM) has showed efficacy and safety at ameliorating inflammation and albuminuria in diabetic patients. In this review, we sketch underlying mechanisms of renal fibrosis in DN, including oxidative stress (OS) generation, OS-elicited ASK1-p38/JNK activation. Also, we briefly summarize the current status of CHM treating DN by improving renal fibrosis. The treatment of DN through inhibiting ASK1 activation to alleviate renal fibrosis in DN with CHM will promote the discovery of novel therapeutic targets for DN and provide a beneficial therapeutic method for DN.